Le corps entre sacré et profane : la réforme des pratiques pèlerines en Égypte (xixe-xxe siècles) - Catherine Mayeur-Jaouen (Revue des Mondes Musulmans et de la Méditerranée, 2006)
The annual festivals to the shrines of the saints – the “mouleds” – are among the main features of the Egyptian popular religion, for the Copts and for the Muslims as well. These mouleds began at the end of the Mamluk period and were carefully described by those who criticezed them, the muslim reformers at the end of the 19th century and at the beginning of the 20th century. The European travellers were pleased to describe these popular festivals, with this typical mixture of religious medieval tradition and scandal. All agree on denouncing the exhibition of the body which characterizes these mouleds : the body is the main vehicle for sacred rituals. What disturbs the reformers and travellers is that the pilgrims associate devotion with dance, prayer with the merry-go-rounds, the Divine with the obscene pantomime, and miracles with prostitution.Since the end of the nineteenth century, the Egyptian state and the muslim clerks have joined their efforts to spiritualize the muslim pilgrimages. So had the Coptic Revival did, for Coptic pilgrimages, more recently. This recent distinction between sacred and profane means to separate body and soul. The negation of popular culture has become the mainstream religion : there is no longer a place for the body in this new conception of the sacred.